A community edutainment intervention for gender-based violence, sexual and reproductive health, and maternal and child health in rural Senegal: A process evaluation - Le Port, Agnes; Seye, Moustapha; Heckert, Jessica; Peterman, Amber; Tchamwa, Annick Nganya; Dione, Malick; Fall, Abdou Salam; Hidrobo, Melissa (BioMed Central, 2022)
Background: Edutainment aims to spread educational messages in an entertaining way, and often reaches large audiences. While studies increasingly report the impacts of edutainment interventions, there is limited context-specific evidence on the underlying processes and barriers to effective delivery, especially in rural areas. This article presents results from a process evaluation of a community-based edutainment intervention designed to improve knowledge, attitudes, and practices on gender-based violence (GBV), sexual and reproductive health (SRH), and maternal and child health. The intervention focused on the television series, C’est la Vie!, screened through biweekly film clubs in rural Senegal and included post-screening discussions and thematic workshops, meant to reinforce messages, increase knowledge, and change social norms. The objectives of this study were to assess intervention adaptation, implementation fidelity, participants’ responsiveness or engagement, and series appropriateness. Methods: The intervention was implemented from December 2019 to March 2020 in 120 villages in Kaolack and Kolda regions of Senegal, and targeted adolescent girls and young women aged 14 to 34. The process evaluation was carried out in March 2020 in 14 villages using: i) individual semi-structured interviews with implementers (n = 3), village chiefs (n = 8), married women (n = 9), adolescent girls (n = 8), and men (n = 8); ii) focus groups with men (n = 7, 29 participants) and women (n = 10, 100 participants); and iii) observations of screening sessions (n = 4) and post-screening discussions (n = 2). Data were analyzed using thematic and content analysis. Results: The results highlight that adaptation of the intervention helped reach the target population and improved participant attendance, but might have compromised fidelity to original design, as intervention components were shortened and modified for rural delivery and some facilitators made ad hoc modifications. The screenings coverage and frequency were adequate; however, their duration was shortened due to COVID-19 restrictions in Senegal. Participant responsiveness was excellent, as was the series appropriateness for most topics, including GBV. SRH remains a sensitive topic for youth, especially when the film clubs included non-peers, such as slightly older women. Conclusions: This study showed that using film clubs to deliver sensitive edutainment content in rural areas is feasible and has potential for scale-up.